Research on the thermal performance of matrix cooling channel with response surface methodology. (25th October 2016) - Bu, Shi; Yang, Zipeng; Zhang, Wenbin; Liu, Huannan; Sun, Haiou
Highlights: Detailed heat transfer distribution is obtained in matrix cooling channel. Effect of geometry on the thermal performance is studied systematically. There exists optimum rib angle between 30-deg and 60-deg. Thermal performance is plotted on response surface for optimal design. Abstract: In this investigation, three structural parameters are defined for matrix cooling channel: rib angle, rib-to-subchannel ratio and rib density, in a certain typical rectangular cooling space. A carefully designed wind tunnel experiment using transient liquid crystal technique is carried out to obtain surface Nusselt number distribution and pressure drop. The measured data is used to validate the computational method. Turbulence SST model is adopted to study the performance of 13 different matrix channels in Reynolds number range of 5000–90, 000. A response surface method is used to fit the CFD solutions and polynomial expressions are established to calculate friction factor ratio (f/f0) and heat transfer enhancement (Nu/Nu0). Variation of thermal performance factor (TPF = (Nu/Nu0)/(f/f0)1/3) versus rib angle, rib-to subchannel ratio and rib density is plotted. The result shows that different structural parameters have to be considered simultaneously in order to improve matrix thermal performance. The comparison of different cases indicates that although smaller rib angle or narrower subchannel can produce very strong local heat transfer, the uniformity is sacrificed.